Research on Apparel Enterprise Management and Marketing Strategy Based on Brand Value Identification (Journal of economic and management development research, 2026)
This study examines how apparel enterprises systematically construct and communicate their brand core values through marketing strategies, thereby driving consumer purchase decisions based on cultural identification. Moving beyond traditional consumer behavior analysis, it explores how management translates abstract cultural concepts into actionable product strategies and marketing activities. Employing Bourdieu’s “Cultural Capital” theory and McCracken’s “Meaning Transfer Model” as its analytical framework, this research conducts in-depth case studies of multiple brands spanning both sportswear and luxury segments. The findings reveal that successful apparel brands essentially function as effective “cultural capital operators” and “meaning management experts.” By anchoring themselves within specific social fields through precise positioning, these brands adopt integrated strategies—including product innovation, content narrative, community engagement, and channel orchestration—to systematically encode and transfer cultural meaning, thereby fostering strong value recognition and a sense of identity among consumers. This study argues that value-identification-oriented brand management constitutes a strategic alignment with and empowerment of consumers’ identity projects. This process requires firms to maintain strategic focus while leveraging data-driven precision and operational agility to build sustainable competitive differentiation.
Keywords: Brand value identification; Cultural capital; Meaning transfer; Apparel enterprise management; Marketing strategy